AB0797 Gait abnormalities in rheumatic patients with temporomandibular joint involvement. (23rd January 2014) - Melchiorre, D.; Rinaldi, L. A.; Maresca, M.; Simoni, D.; Monaco, V.; Di Bari, M.; Matucci-Cerinic, M.
Abstract : Background: The relationship between temporomandibular joint disorders (TMD) and alterations of posture and gait has been widely discussed in several investigations, reaching different and sometimes opposite conclusions Objectives: To investigate whether TMD in early rheumatoid and psoriatic arthritis could influence gait pattern, assessed by computerized gait analysis with dual task (DT) paradigm. Methods: Two groups of subjects were examined: a group of 30 patients with TMD in early rheumatoid or psoriatic arthritis without signs of involvement of other joints and a control group of 30 healthy subjects. Both temporomandibular joints were examined by ultrasound imaging in every subject. Gait analysis with a photogrammetric system during treadmill walking was performed. In DT procedure, treadmill walking was associated with a cognitive task. The coordination patterns thigh-leg, leg-foot and thigh-foot were analyzed. Results: Sonographic findings showed joint effusion and alterations of condylar profile in all patients. Spatio-temporal parameters, during treadmill walking, did not show significant differences between controls and patients in single and dual task. Patients showed an asymmetric behavior of the coordination pattern leg-foot in DT procedure, during swing and stance phase of walking. In healthy subjects no significant difference of the coordination pattern leg-foot was observed. Conclusions: DT procedure assessed the relationship between TMD and changes of the coordination pattern leg-foot during walking. DT shows that patients with TMD involvement develop an inadequate walking performance. These data focus the attention on the presence of postural abnormalities and gait alterations in patients with TMD, suggesting its evaluation in arthritides to obtain a timely correction of the gait modifications. Disclosure of Interest: None Declared